Volume 2C: Turbomachinery 2015
DOI: 10.1115/gt2015-43193
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Increase in Centrifugal Compressor With Open Impeller by Using Curvilinear Element Blade

Abstract: The effect of curvilinear element blade on open-type centrifugal impeller is numerically examined in this research. We compared four different open-type centrifugal impellers. Two of them were linear element blade impellers: one has a positive tangential lean to the rotation at the outlet and the other has negative tangential lean. The other two were curvilinear element blade impellers having different tangential lean profiles. Numerical simulation of steady flow was conducted in one-blade path model with inle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The authors concluded that an efficiency increase of about 1.5% was mainly achieved due to a shock strength reduction in the inducer of the impeller. Another remarkable optimization of a process gas compressor with a shrouded impeller was made by Hiradate et al (2014), which was later experimentally verified by Tsukamoto et al (2015). Due to the use of curvilinear blade stacking and thus a modification of lean, an efficiency improvement of 2.1% could be achieved.…”
Section: Introductionmentioning
confidence: 96%
“…The authors concluded that an efficiency increase of about 1.5% was mainly achieved due to a shock strength reduction in the inducer of the impeller. Another remarkable optimization of a process gas compressor with a shrouded impeller was made by Hiradate et al (2014), which was later experimentally verified by Tsukamoto et al (2015). Due to the use of curvilinear blade stacking and thus a modification of lean, an efficiency improvement of 2.1% could be achieved.…”
Section: Introductionmentioning
confidence: 96%
“…Efficiency and pressure ratios are influenced by various factors, such as the velocity coefficient, energy head coefficient, rotational speed, blade height, inlet radius, and radial distance [19]. A comparative study of different blade types revealed that impellers with a trailing edge bend opposite to the rotating direction reduced the pressure difference near the blade tip, thereby minimizing tip leakage loss and improving compressor performance [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, just as the author said, the static pressure distribution at cross section in blade passage is not enough to support the explanation. Tsukamoto et al (2015Tsukamoto et al ( , 2019 studied the effects of the bow trailing edge on an open-type impeller, and the efficiency improvement of the impeller and vaneless diffuser was attributed to the blade force brought by the positive bow to reduce the tip leakage flow at the impeller outlet. Mosdzien et al (2018) and Wittrock et al (2018) improved the performance of two different centrifugal compressors by using bow impeller blades generating from numerical optimize method.…”
Section: Introductionmentioning
confidence: 99%